Fuzzy speed controller for DC motor drives - Muhammad Izzuddin, Jaafar (2013)
This project is to design and develop a speed control method using fuzzy logic for smart temperature control. Fuzzy logic technique is a smart control system which able to make decision on multi-value logic. Fuzzy logic system is analyzed using word rather than numbers, so it makes fuzzy logic closer to human intuition and able to utilize tolerance for imprecision. The fuzzy logic control will be implemented by using a micro controller PIC 18F4550 which able to receive and sending the data and become a platform for fuzzy inference system. Sensor will be used to detect the variable while DC motor will be used as output or actuator. Clanguage programming will be used as assemble language for programming and develop the algorithm and interface.